Dental Workforce Trends: A National Study of Gender Diversity and Practice Patterns. (February 2021) - Surdu, Simona; Mertz, Elizabeth; Langelier, Margaret; Moore, Jean
The dental workforce is increasingly gender diverse. This study analyzed gender differences in dental practice using the American Dental Association's 2010-2016 Masterfile and the 2017 Survey of Dental Practice. Between 2010 and 2016, the proportion of women working in dentistry increased from 24.5% to 29.8%. Overall, female dentists were more racially/ethnically diverse, more likely to be foreign-trained, and more likely to work in pediatric dentistry than male dentists. The likelihood of female dentists working as employees, part-time, and/or in metropolitan areas was 1.2 to 4.2 times greater compared with male dentists. Female solo practitioners were 1.2 to 1.8 times more likely to provide services to children and patients covered by public insurance than male solo practitioners. Gender diversification in dentistry and other factors, including generational differences and changes in the dental service delivery system and public policy, will continue to reshape the delivery of oral health services.